Leukocyte populations detection in young athletes in resting phase based on scatter properties using a Flow Cytometric approach - Ornela Marko; Klotilda Vrenjo; Majlind Sulçe (Central European Journal of Sport Sciences and Medicine)
Complete blood count analysis has a major importance as a first laboratory evaluation. In particular data obtained from complete blood count are relevant to correctly diagnose and follow up different medical conditions. In athletes, medical examinations and laboratory test are mandatory, especially when a sportive event will soon take place. Different automatic techniques are used to evaluate percentages of different leukocyte populations with a high accuracy. Flow cytometry represents a technology that is mainly used to diagnose different lymphoproliferative and myeloproliferative neoplastic disorders. In this study 127 samples from clinically healthy young athletes were collected and analyzed with both flow cytometry and automatic method to evaluate the usefulness of flow cytometry in detecting different leukocyte populations based on their scatter properties. Results showed that flow cytometry is a reliable technique having showed a high accuracy for different cell populations. Intra class correlation coefficient was >0.80 for all populations showing a high correlation between the two methods. However, a higher number of cases, the involvement of other automatic techniques are mandatory to confirm these results.